Covid-19 Pandemi sürecinde evde uygulanan yüksek yogunluklu aralikli antr nmanlar profesyonel hentbol oyuncularinin formda kalmalarini saglayabilir mi? - Bilge, M.; Deliceoglu, G.; Isik, Ö. (Turkish Studies, 2020)
The purpose of the research is to show professional handballers that high-density exercises applied in the home environment are similar to aerobic capacity in the field environment. The research group is 16 national handball players with an average age of 24.67-5.71 years, length of 186.69-6.40 cm and body weight 89.63-8.64 kg. Polar clock was used to detect heart beat counts during exercises performed by handball playersin the home environment. Five weeks of exercises of different intensity are divided into 4 different intensity exercise groups. Handball players recorded heart rate (HR) and perceived difficulty at the end of their workouts in the home environment. According to the findings, HRmax values in the field environment have a moderate relationship with some exercise Rating Perceived Exertion (RPE) values with MaxRPE, which is a high level of relationship with some exercise HR values of some exercise HR values of different densities. As a result, while the training HR values taken from handball players are planned to resemble the training load, it may be suggested that some training structures do not capture the target HR value, that RPE values taken from handball players are subjective, as well as verifying according to the HR value during training.